Hydroxyl-rich nickel magnesium silicate nanosheet material, preparation method and application thereof, supported noble metal catalyst and application thereof
By using hydroxyl-rich nickel-magnesium silicate nanosheet materials as support to prepare a supported precious metal catalyst, the existing CO priority oxidation catalyst has been solved, and the CO priority oxidation reaction effect with high activity and wide temperature window is achieved .
Patent Information
- Application Number
- CN202411510109.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing CO priority oxidation catalysts have low activity and a narrow CO-PROX temperature window, making it difficult to meet the demand for high activity and wide temperature windows in fuel cells.
Using hydroxyl-rich nickel-magnesium silicate nanosheet material as a support, a supported precious metal catalyst is prepared through hydrothermal reaction and calcination steps to improve catalytic activity and broaden the temperature window.
The combination of high catalytic activity and wide temperature windows in CO priority oxidation reaction is achieved, which significantly improves the stability and reaction efficiency of the catalyst.
Smart Images

Figure CN119390079A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field related to carbon monoxide preferential oxidation materials, and in particular to a hydroxyl-rich nickel magnesium silicate nanosheet material and a preparation method and application thereof, a supported noble metal catalyst and application thereof. Background Art
[0002] With the global consensus on green, low-carbon and sustainable development, fuel cells, as a clean energy technology, can reduce the use of fossil energy, reduce carbon dioxide emissions, and combat climate change and environmental pollution. Therefore, fuel cells, as a mobile, efficient and pollution-free power source, have become the focus of world attention. Among them, proton exchange membrane fuel cells (PEMFC) are considered to be the most promising energy conversion and storage devices due to their high energy density, long working life, good low-temperature start-up performance and low operating temperature. However, the device requires high-purity H2 fuel gas. Usually, industrial hydrogen is mainly obtained from hydrocarbon reforming and water-gas shift reactions, and contains about 1% CO residue. It can easily poison the anode Pt electrode of PEMFC, and the CO content must be controlled below 100ppm. The CO preferential oxidation reaction (CO-PROX) is considered to be an effective way to solve this problem. Moreover, the CO preferential oxidation reactor is between the water-gas shift reactor (200℃) and the fuel cell (80~100℃). Therefore, it is extremely urgent to develop catalytic materials with high activity, high selectivity and a wide CO-PROX temperature window.
[0003] Supported noble metal catalysts have been widely studied as a typical CO preferential oxidation catalyst, in which the carrier is crucial. At present, the commonly used carriers for CO preferential oxidation catalysts are oxides, such as γ-Al2O3, SiO2, MgO, TiO2, etc. The activity of supported noble metal catalysts prepared using these carriers needs to be improved, and the CO-PROX temperature window is narrow. Summary of the invention
[0004] The purpose of the present invention is to provide a hydroxyl-rich nickel magnesium silicate nanosheet material and its preparation method and application, a supported noble metal catalyst and its application. The present invention uses the hydroxyl-rich nickel magnesium silicate nanosheet material as a carrier, and the obtained supported noble metal catalyst exhibits high catalytic activity and a wide temperature window in the CO preferential oxidation reaction.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a hydroxyl-rich nickel magnesium silicate nanosheet material, which is composed of hydroxyl-rich nickel magnesium silicate nanosheets, wherein the surface of the hydroxyl-rich nickel magnesium silicate nanosheets contains hydroxyl groups and NiO; the chemical formula of the hydroxyl-rich nickel magnesium silicate nanosheets is shown in Formula 1:
[0007] (Ni x Mg 1-x )2Si2O5(OH)4 Formula 1;
[0008] Wherein, x is 0.45 to 0.55;
[0009] According to X-ray photoelectron spectroscopy analysis, the relative content of hydroxyl groups in the hydroxyl-rich nickel magnesium silicate nanosheet material is 70-75%, and the relative content of NiO is 25-30%.
[0010] Preferably, the lateral size of the hydroxyl-rich nickel magnesium silicate nanosheets is 500-800 nm.
[0011] The present invention provides a method for preparing the hydroxyl-rich nickel magnesium silicate nanosheet material described in the above scheme, comprising the following steps:
[0012] A water suspension of silicon dioxide, a soluble magnesium salt, a soluble nickel salt, an acid solution and a hydroxide solution are mixed, and the resulting mixture is subjected to a hydrothermal reaction to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor; the molar ratio of Ni in the soluble nickel salt to Mg in the soluble magnesium salt is x:(1-x), wherein x is 0.45 to 0.55;
[0013] The hydroxyl-rich nickel magnesium silicate nanosheet material precursor is calcined to obtain the hydroxyl-rich nickel magnesium silicate nanosheet material; the calcination temperature is 400-500°C.
[0014] Preferably, the molar ratio of silicon dioxide to Ni in the soluble nickel salt is (0.75-3.75):1;
[0015] The molar ratio of the silicon dioxide to the hydroxide in the hydroxide solution is 3:(4-8);
[0016] The acid solution includes a boric acid solution; the molar ratio of the silicon dioxide to the boric acid in the boric acid solution is (1-2):5.
[0017] Preferably, the temperature of the hydrothermal reaction is 160-200° C. and the time is 12-24 hours.
[0018] Preferably, the calcination holding time is 5 to 12 hours.
[0019] The present invention provides the use of the hydroxyl-rich nickel magnesium silicate nanosheet material described in the above scheme or the hydroxyl-rich nickel magnesium silicate nanosheet material prepared by the preparation method described in the above scheme as a catalyst carrier.
[0020] The present invention provides a supported noble metal catalyst, comprising a carrier and a noble metal supported on the carrier; the carrier is the hydroxyl-rich nickel magnesium silicate nanosheet material described in the above scheme or the hydroxyl-rich nickel magnesium silicate nanosheet material prepared by the preparation method described in the above scheme.
[0021] The present invention provides the use of the supported noble metal catalyst described in the above scheme in the CO preferential oxidation reaction.
[0022] The present invention provides a hydroxyl-rich nickel magnesium silicate nanosheet material, which is composed of hydroxyl-rich nickel magnesium silicate nanosheets, wherein the surface of the hydroxyl-rich nickel magnesium silicate nanosheets contains hydroxyl groups and NiO; the chemical formula of the hydroxyl-rich nickel magnesium silicate nanosheets is shown in Formula 1: (Ni x Mg 1-x )2Si2O5(OH)4 formula 1; wherein x is 0.45-0.55; through X-ray photoelectron spectroscopy analysis, the relative content of hydroxyl in the hydroxyl-rich nickel magnesium silicate nanosheet material is 70-75%, and the relative content of NiO is 25-30%.
[0023] The surface of the hydroxyl-rich nickel magnesium silicate nanosheet material provided by the present invention contains hydroxyl groups and NiO. When the material is used as a carrier, the OH on the surface can not only utilize the noble metal to stabilize the load, enhance the interaction between the metal and the carrier, avoid the noble metal agglomeration and deactivation, and improve the catalytic stability, but also effectively participate in the reaction process and act as an activated oxygen species; NiO can also effectively activate molecular oxygen. The design of the overall catalyst effectively avoids the competitive adsorption of CO and O2, enhances oxygen activation, thereby improving the catalytic activity of the catalyst and broadening the corresponding temperature operation window.
[0024] In addition, the hydroxyl-rich nickel magnesium silicate provided by the present invention has a nanosheet morphology, which is different from the conventional tubular structure. The nanosheet morphology is more conducive to the loading of precious metals and the exposure of catalytic active sites, thereby improving the catalytic activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 XRD patterns of sample 1# and samples 6# to 10#;
[0026] Figure 2 IR spectra of sample 1# and samples 6# to 8#;
[0027] Figure 3 TEM image of sample 1#;
[0028] Figure 4 This is the TEM image of sample 7#;
[0029] Figure 5 The catalytic performance diagram of the Pt-loaded catalysts prepared using samples 1# to 10# as carriers;
[0030] Figure 6 This is a stability test chart of the Pt-loaded catalyst prepared using sample 7# as the carrier. DETAILED DESCRIPTION
[0031] The present invention provides a hydroxyl-rich nickel magnesium silicate nanosheet material, which is composed of hydroxyl-rich nickel magnesium silicate nanosheets, wherein the surface of the hydroxyl-rich nickel magnesium silicate nanosheets contains hydroxyl groups and NiO; the chemical formula of the hydroxyl-rich nickel magnesium silicate nanosheets is shown in Formula 1:
[0032] (Ni x Mg 1-x )2Si2O5(OH)4 Formula 1;
[0033] Wherein, x is 0.45 to 0.55;
[0034] According to X-ray photoelectron spectroscopy analysis, the relative content of hydroxyl groups in the hydroxyl-rich nickel magnesium silicate nanosheet material is 70-75%, and the relative content of NiO is 25-30%.
[0035] In the present invention, the x is preferably 0.5.
[0036] In the present invention, the hydroxyl-rich nickel magnesium silicate nanosheet material is a standard lizardite structure.
[0037] In the present invention, when x=0.5, through X-ray photoelectron spectroscopy analysis (XPS fitting), the relative content of hydroxyl in the hydroxyl-rich nickel magnesium silicate nanosheet material is 72%, and the relative content of NiO is 28%.
[0038] In the present invention, the lateral size of the hydroxyl-rich nickel magnesium silicate nanosheet is preferably 500-800 nm. Conventional hydroxyl-rich nickel magnesium silicate has a tubular morphology, while the hydroxyl-rich nickel magnesium silicate provided by the present invention has a nanosheet morphology, which is more conducive to the loading of precious metals and the exposure of catalytic active sites, thereby improving catalytic activity.
[0039] In addition, in the related technology, hydroxyl-rich nickel magnesium silicate is mainly used in the lubrication field, and no one has reported using it as a catalyst carrier.
[0040] In the present invention, the surface of the hydroxyl-rich nickel magnesium silicate nanosheet contains hydroxyl groups and NiO, and it is used as a carrier. The OH on the surface can not only utilize the stable loaded precious metal, enhance the interaction between the metal and the carrier, avoid the agglomeration and deactivation of the precious metal, and improve the catalytic stability, but also effectively participate in the reaction process and act as an activated oxygen species; NiO can also effectively activate molecular oxygen. The design of the overall catalyst effectively avoids the competitive adsorption of CO and O2, enhances oxygen activation, thereby improving the catalytic activity of the catalyst and broadening the corresponding temperature operation window.
[0041] The present invention provides a method for preparing the hydroxyl-rich nickel magnesium silicate nanosheet material described in the above scheme, comprising the following steps:
[0042] A water suspension of silicon dioxide, a soluble magnesium salt, a soluble nickel salt, an acid solution and a hydroxide solution are mixed, and the resulting mixture is subjected to a hydrothermal reaction to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor; the molar ratio of Ni in the soluble nickel salt to Mg in the soluble magnesium salt is x:(1-x), wherein x is 0.45 to 0.55;
[0043] The hydroxyl-rich nickel magnesium silicate nanosheet material precursor is calcined to obtain the hydroxyl-rich nickel magnesium silicate nanosheet material; the calcination temperature is 400-500°C.
[0044] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known in the art.
[0045] The invention mixes a water suspension of silicon dioxide, a soluble magnesium salt, a soluble nickel salt, an acid solution and a hydroxide solution, and performs a hydrothermal reaction on the obtained mixed solution to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor.
[0046] In the present invention, the aqueous suspension of silicon dioxide is preferably obtained by dispersing silicon dioxide in water; the concentration of the aqueous suspension of silicon dioxide is preferably 0.005-0.02 g / mL. The present invention has no special requirements for the dispersion method, as long as the silicon dioxide can be evenly dispersed, for example, by ultrasonic dispersion for 10-30 minutes. In the present invention, the silicon dioxide is preferably commercial silicon dioxide nanospheres.
[0047] In the present invention, the soluble magnesium salt preferably includes at least one of magnesium chloride, magnesium nitrate and magnesium sulfate; the soluble nickel salt preferably includes at least one of nickel chloride, nickel nitrate and nickel sulfate.
[0048] In the present invention, the soluble magnesium salt and the soluble sodium salt are preferably used in the form of an aqueous solution; more preferably, the soluble magnesium salt and the soluble sodium salt are dissolved in water together to form a metal salt soluble solution, which is used in the form of a metal salt aqueous solution. The present invention has no special requirements on the concentration of the metal salt aqueous solution.
[0049] In the present invention, the molar ratio of Ni in the soluble nickel salt to Mg in the soluble magnesium salt is x:(1-x), wherein x is 0.45 to 0.55. In particular, when the molar ratio of the two is 0.5:0.5, the supported noble metal catalyst prepared by using the obtained hydroxyl-rich nickel magnesium silicate nanosheet material as a carrier exhibits better catalytic activity and a wider temperature window in the CO preferential oxidation reaction.
[0050] In the present invention, the molar ratio of the silicon dioxide to Ni in the soluble nickel salt is preferably (0.75-3.75):1. In a specific embodiment, the molar ratio of the silicon dioxide to Ni in the soluble nickel salt can be 0.75:1, 1:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1 or 3.75:1.
[0051] In the present invention, the acid solution preferably includes a boric acid solution; the concentration of the boric acid solution is preferably 0.75-1.5 mol / L; in a specific embodiment of the present invention, the concentration of the boric acid solution may be 0.75 mol / L, 1 mol / L, 1.25 mol / L or 1.5 mol / L. In the present invention, the molar ratio of the silicon dioxide to the boric acid in the boric acid solution is preferably (1-2):5. In a specific embodiment, the molar ratio of the silicon dioxide to the boric acid in the boric acid solution may be 1:5, 1.5:5 or 2:5. In the present invention, the role of the boric acid is to reduce the reactivity, thereby controlling the rate of reaction nucleation, and the morphology of the hydroxyl-rich nickel magnesium silicate can be well controlled.
[0052] In the present invention, the hydroxide solution preferably includes a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is preferably 0.4-0.8 mol / L. In a specific embodiment of the present invention, the concentration of the sodium hydroxide solution may be 0.4 mol / L, 0.5 mol / L, 0.6 mol / L or 0.8 mol / L. In the present invention, the molar ratio of the silicon dioxide to the hydroxide in the hydroxide solution is preferably 3:(4-8). In a specific embodiment, the molar ratio of the silicon dioxide to the hydroxide in the hydroxide solution may be 3:4, 3:5, 3:6, 3:7 or 3:8.
[0053] In the present invention, the mixing of the water suspension of silicon dioxide, the soluble magnesium salt, the soluble nickel salt, the acid solution and the hydroxide solution preferably comprises: adding the soluble magnesium salt and the soluble nickel salt to the water suspension of silicon dioxide under stirring conditions, then dripping the acid solution, and finally dripping the hydroxide solution. After all the raw materials are added, the present invention preferably continues stirring for 10 to 30 minutes.
[0054] In the present invention, the temperature of the hydrothermal reaction is preferably 160-200°C. In a specific embodiment of the present invention, the temperature of the hydrothermal reaction can be 160°C, 170°C, 180°C, 190°C or 200°C. The time of the hydrothermal reaction is preferably 12-24h. In a specific embodiment of the present invention, the time of the hydrothermal reaction can be 12h, 15h, 18h, 20h or 24h. In the hydrothermal reaction process of the present invention, SiO2 and OH - Reaction to generate SiO3 2- and H2O, then Mg 2+、Ni 2+ With SiO3 2- and OH - The reaction generates (Ni x Mg 1-x )2Si2O5(OH)4, the acid plays a role in regulating the microenvironment during the hydrothermal reaction.
[0055] After the hydrothermal reaction is completed, the present invention preferably performs solid-liquid separation on the obtained reaction product liquid, washes it, and dries the obtained wet solid to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor.
[0056] The present invention has no special requirements for the solid-liquid separation method, and a solid-liquid separation method well known in the art can be used, such as suction filtration. In the present invention, the washing liquid used for washing preferably includes distilled water and ethanol. The present invention has no special requirements for the drying, and a drying process well known in the art can be used. In the embodiment of the present invention, it is specifically dried at 60°C overnight.
[0057] In the present invention, the surface of the hydroxyl-rich nickel magnesium silicate nanosheet material precursor does not contain NiO.
[0058] After obtaining the hydroxyl-rich nickel magnesium silicate nanosheet material precursor, the present invention bakes the hydroxyl-rich nickel magnesium silicate nanosheet material precursor to obtain the hydroxyl-rich nickel magnesium silicate nanosheet material.
[0059] Before the calcination, the hydroxyl-rich nickel magnesium silicate nanosheet material precursor is preferably ground. The present invention has no special requirements for the grinding, and it only needs to be ground evenly.
[0060] In the present invention, the calcination is preferably carried out in an air atmosphere; the calcination temperature is preferably 400-500°C, more preferably 450°C; the calcination holding time is preferably 5-12h, and in a specific embodiment of the present invention, the calcination holding time can be 5h, 7h, 9h, 10h or 12h. In the present invention, the rate of heating to the calcination temperature is preferably 1-5°C / min.
[0061] The present invention causes the loss of OH on the surface of hydroxy nickel magnesium silicate and the precipitation of NiO by calcination, and the hydroxyl and NiO contents on the surface of the hydroxyl-rich nickel magnesium silicate nanosheet material can be effectively regulated by adjusting the calcination temperature.
[0062] The present invention provides the use of the hydroxyl-rich nickel magnesium silicate nanosheet material described in the above scheme or the hydroxyl-rich nickel magnesium silicate nanosheet material prepared by the preparation method described in the above scheme as a catalyst carrier.
[0063] The present invention provides a supported noble metal catalyst, comprising a carrier and a noble metal supported on the carrier; the carrier is the hydroxyl-rich nickel magnesium silicate nanosheet material described in the above scheme or the hydroxyl-rich nickel magnesium silicate nanosheet material prepared by the preparation method described in the above scheme.
[0064] In the present invention, the noble metal preferably includes one or more of Pt, Au, Ru and Rh. In the present invention, the loading amount of the noble metal is preferably 0.2-5wt% (the mass percentage of the noble metal to the carrier). In a specific embodiment of the present invention, the loading amount of the noble metal can be 0.2wt%, 0.5wt%, 1.0wt%, 1.5wt%, 2.0wt%, 3.0wt%, 4.0wt% or 5wt%.
[0065] The present invention has no special requirements for the preparation method of the supported precious metal catalyst, and it can be prepared by methods well known in the art. In the embodiment of the present invention, it is prepared by a wet impregnation process; the preparation method of the supported precious metal catalyst preferably includes the following steps: dispersing the carrier in water to obtain a carrier dispersion; adding an aqueous solution of precious metal ions to the carrier dispersion for impregnation; adding a reducing agent to the impregnation system to reduce the precious metal ions to precious metals, and separating the solid and liquid to obtain a supported precious metal catalyst.
[0066] The present invention does not make any special requirements on the specific details of each step in the above-mentioned preparation method, which is a conventional technical means in the field.
[0067] The present invention provides the use of the supported noble metal catalyst described in the above scheme in the CO preferential oxidation reaction. In the present invention, the temperature of the CO preferential oxidation reaction is preferably 30 to 200°C. In a specific embodiment of the present invention, the temperature of the CO preferential oxidation reaction can be 30°C, 50°C, 70°C, 100°C, 150°C, 180°C or 200°C.
[0068] The present invention has no special requirements for the pressure and space velocity of the CO preferential oxidation reaction, and the reaction pressure and space velocity known in the art can be used. In the embodiment of the present invention, the reaction pressure is 0.25Mpa and the space velocity is 60000h -1 ; In terms of volume percentage, the reaction gas composition is 1% CO, 1.25% O2, 50% H2, and He balance.
[0069] The hydroxyl-rich nickel magnesium silicate nanosheet material, preparation method and application thereof, supported noble metal catalyst and application thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0070] Comparative Example 1 Preparation of Sample 1# Precursor with a Magnesium-Ni Molar Ratio of 0.5:0.5
[0071] 0.006mol of SiO2 nanospheres were dispersed in 20mL of distilled water and ultrasonicated for 10min to form a uniform suspension. Then 4mmol of magnesium chloride hexahydrate and 4mmol of nickel chloride hexahydrate were dissolved in 20mL of distilled water, and 15mmol of boric acid and 8mmol of sodium hydroxide were dissolved in 20mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the SiO2 suspension in turn, and magnetic stirring was carried out for 10min at room temperature. Then the reactants were transferred to a 100mL reactor and reacted at 180℃ for 12h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60℃ overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor with a nickel-magnesium molar ratio of 0.5:0.5, which was recorded as sample 1#. XPS characterization showed that the relative content of hydroxyl was 100% and the relative content of NiO was 0.
[0072] Comparative Example 2 Preparation of Sample 2# Precursor with a Magnesium-Ni Molar Ratio of 0.2:0.8
[0073] 0.006 mol of SiO2 nanospheres were dispersed in 20 mL of distilled water and ultrasonicated for 10 min to form a uniform suspension. Then 1.6 mmol of magnesium chloride hexahydrate and 6.4 mmol of nickel chloride hexahydrate were dissolved in 20 mL of distilled water, and 15 mmol of boric acid and 8 mmol of sodium hydroxide were dissolved in 20 mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the suspension of SiO2 in turn, and magnetic stirring was carried out for 10 min at room temperature. Then the reactants were transferred to a 100 mL reactor and reacted at 180 ° C for 12 h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60 ° C overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor with a nickel-magnesium molar ratio of 0.2:0.8, which was recorded as sample 2#.
[0074] Comparative Example 3 Preparation of sample 3# with a magnesium-nickel molar ratio of 0.4:0.6 and rich in hydroxyl nickel magnesium silicate nanosheet material
[0075] 0.006 mol of SiO2 nanospheres were dispersed in 20 mL of distilled water and ultrasonicated for 10 min to form a uniform suspension. Then 3.2 mmol of magnesium chloride hexahydrate and 4.8 mmol of nickel chloride hexahydrate were dissolved in 20 mL of distilled water, and 15 mmol of boric acid and 8 mmol of sodium hydroxide were dissolved in 20 mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the SiO2 suspension in turn, and magnetic stirring was carried out for 10 min at room temperature. Then the reactants were transferred to a 100 mL reactor and reacted at 180 ° C for 12 h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60 ° C overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor with a nickel-magnesium molar ratio of 0.4:0.6, which was recorded as sample 3#.
[0076] Comparative Example 4 Preparation of Sample 4# Precursor with a Magnesium-Ni Molar Ratio of 0.6:0.4
[0077] 0.006 mol of SiO2 nanospheres were dispersed in 20 mL of distilled water and ultrasonicated for 10 min to form a uniform suspension. Then 4.8 mmol of magnesium chloride hexahydrate and 3.2 mmol of nickel chloride hexahydrate were dissolved in 20 mL of distilled water, and 15 mmol of boric acid and 8 mmol of sodium hydroxide were dissolved in 20 mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the SiO2 suspension in turn, and magnetic stirring was carried out for 10 min at room temperature. Then the reactants were transferred to a 100 mL reactor and reacted at 180 ° C for 12 h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60 ° C overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor with a nickel-magnesium molar ratio of 0.6:0.4, which was recorded as sample 4#.
[0078] Comparative Example 5 Preparation of Sample 5# Precursor with a Magnesium-Ni Molar Ratio of 0.8:0.2
[0079] 0.006 mol of SiO2 nanospheres were dispersed in 20 mL of distilled water and ultrasonicated for 10 min to form a uniform suspension. Then 6.4 mmol of magnesium chloride hexahydrate and 1.6 mmol of nickel chloride hexahydrate were dissolved together in 20 mL of distilled water, and 15 mmol of boric acid and 8 mmol of sodium hydroxide were dissolved in 20 mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the suspension of SiO2 in turn, and magnetic stirring was carried out for 10 min at room temperature. Then the reactants were transferred to a 100 mL reactor and reacted at 180 ° C for 12 h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60 ° C overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor with a nickel-magnesium molar ratio of 0.8:0.2, which was recorded as sample 5#.
[0080] Comparative Example 6 Preparation of sample 6# with a magnesium-nickel molar ratio of 0.5:0.5 and calcined at 250°C to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material
[0081] 0.006mol of SiO2 nanospheres were dispersed in 20mL of distilled water and ultrasonicated for 10min to form a uniform suspension. Then 4mmol of magnesium chloride hexahydrate and 4mmol of nickel chloride hexahydrate were dissolved in 20mL of distilled water, and 15mmol of boric acid and 8mmol of sodium hydroxide were dissolved in 20mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the SiO2 suspension in turn and magnetically stirred for 10min at room temperature. Then the reactants were transferred to a 100mL reactor and reacted at 180℃ for 12h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60℃ overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor. After the precursor was ground evenly, it was calcined at 250℃ for 2h, with a heating rate of 2℃ / min, to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material with a nickel-magnesium molar ratio of 0.5:0.5 calcined at 250℃, which was recorded as sample 6#. XPS characterization showed that the relative content of hydroxyl was 77% and the relative content of NiO was 23%.
[0082] Example 1 Preparation of sample 7# hydroxyl-rich nickel magnesium silicate nanosheet material with a magnesium-nickel molar ratio of 0.5:0.5 and calcined at 450°C
[0083] 0.006mol of SiO2 nanospheres were dispersed in 20mL of distilled water and ultrasonicated for 10min to form a uniform suspension. Then 4mmol of magnesium chloride hexahydrate and 4mmol of nickel chloride hexahydrate were dissolved in 20mL of distilled water, and 15mmol of boric acid and 8mmol of sodium hydroxide were dissolved in 20mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the SiO2 suspension in turn, and magnetic stirring was carried out for 10min at room temperature. Then the reactants were transferred to a 100mL reactor and reacted at 180℃ for 12h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60℃ overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor. After the precursor was ground evenly, it was calcined at 450℃ for 2h with a heating rate of 2℃ / min to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material, which was recorded as sample 7#. XPS characterization showed that the relative content of hydroxyl was 72% and the relative content of NiO was 28%.
[0084] Comparative Example 7 Preparation of sample 8# with a magnesium-nickel molar ratio of 0.5:0.5 and calcined at 650°C to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material
[0085] 0.006mol of SiO2 nanospheres were dispersed in 20mL of distilled water and ultrasonicated for 10min to form a uniform suspension. Then 4mmol of magnesium chloride hexahydrate and 4mmol of nickel chloride hexahydrate were dissolved in 20mL of distilled water, and 15mmol of boric acid and 8mmol of sodium hydroxide were dissolved in 20mL of distilled water and stirred to dissolve. Then the above solutions were slowly added to the SiO2 suspension in turn, and magnetic stirring was carried out for 10min at room temperature. Then the reactants were transferred to a 100mL reactor and reacted at 180℃ for 12h. After the hydrothermal reaction, it was cooled to room temperature, washed and filtered with a large amount of distilled water and ethanol, and dried at 60℃ overnight to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor. After the precursor was ground evenly, it was calcined at 650℃ for 2h, with a heating rate of 2℃ / min, to obtain a hydroxyl nickel magnesium silicate nanosheet material with a nickel-magnesium molar ratio of 0.5:0.5, which was recorded as sample 8#. XPS characterization showed that the relative content of hydroxyl was 63% and the relative content of NiO was 37%.
[0086] Comparative Example 8 Preparation of Sample 9# Hydroxy-Rich Magnesium Silicate Catalyst Support
[0087] Disperse 0.006mol of SiO2 nanospheres in 20mL of distilled water and ultrasonicate for 10min to form a uniform suspension. Then dissolve 8mmol of magnesium chloride hexahydrate, 15mmol of boric acid and 8mmol of sodium hydroxide in 20mL of distilled water and stir to dissolve. Then slowly add the above solutions to the SiO2 suspension in turn and stir magnetically for 10min at room temperature. Then transfer the reactants to a 100mL reactor and react at 180℃ for 12h. . After the hydrothermal reaction, cool to room temperature, wash and filter with a large amount of distilled water and ethanol, and dry at 60℃ overnight to obtain hydroxy magnesium silicate.
[0088] Comparative Example 9 Preparation of Sample 10# Hydroxy-Rich Nickel Silicate Catalyst Support
[0089] Disperse 0.006mol of SiO2 nanospheres in 20mL of distilled water and ultrasonicate for 10min to form a uniform suspension. Then dissolve 8mmol of nickel chloride hexahydrate, 15mmol of boric acid and 8mmol of sodium hydroxide in 20mL of distilled water and stir to dissolve. Then slowly add the above solutions to the SiO2 suspension in turn and stir magnetically for 10min at room temperature. Then transfer the reactants to a 100mL reactor and react at 180℃ for 12h. After the hydrothermal reaction, cool to room temperature, wash and filter with a large amount of distilled water and ethanol, and dry at 60℃ overnight to obtain hydroxy nickel silicate.
[0090] Application Examples 1 to 9 Preparation of Pt-loaded Catalysts
[0091] Samples 1# to 10# were used as carriers, and platinum (0.5wt% Pt, relative to the percentage of the carrier) was loaded onto the various carriers synthesized above by wet impregnation in an H2PtCl6 aqueous solution. Specifically, 0.5g of the carrier was dispersed in 50mL of distilled water, and then the H2PtCl6 aqueous solution was added dropwise, and the entire impregnation process was 2h. Then, 3mL of ice-cooled NaBH4 solution (1mg / mL) was quickly injected into the above-mentioned suspension solution. After stirring for 2h, it was washed with deionized water several times, filtered to remove unreacted H2PtCl6, and the powder was collected and then dried at 70°C to obtain a Pt-loaded catalyst.
[0092] Structural and morphological characterization
[0093] Powder X-ray diffraction was used to analyze the structure of sample 1# and samples 6#~10#, such as Figure 1 As shown, the synthesized samples are hydroxy nickel magnesium silicate with different OH and NiO contents on the surface, wherein samples 1#, #9 and 10# are hydroxy nickel magnesium silicate, hydroxy magnesium silicate and hydroxy nickel silicate nanosheet materials respectively, which are not calcined and have no NiO precipitation on the surface. Samples 6#, 7# and 8# are hydroxy nickel magnesium silicate nanosheet materials obtained by calcining at different temperatures. Figure 1 The diffraction peak at 43.3° is attributed to NiO. As the calcination temperature increases, the diffraction peak intensity gradually becomes stronger, indicating that NiO is gradually precipitated from the surface of the hydroxyl-rich nickel magnesium silicate nanosheet material precursor.
[0094] Sample 1# and samples 6# to 8# were characterized by infrared (IR) to characterize the hydroxyl content. The results are as follows: Figure 2 As shown in the figure, with the increase of calcination temperature, the vibration peak intensity of OH of sample 1#, sample 6#, sample 7# and sample 8# becomes lower and lower, indicating that the hydroxyl content gradually decreases. Therefore, by adjusting the calcination temperature, the hydroxyl and NiO content on the surface of hydroxy nickel magnesium silicate nanosheet material can be effectively adjusted.
[0095] TEM characterization of sample 1# was performed, and the results are as follows Figure 3 As shown, sample 1# has a nanosheet morphology with a lateral size of approximately 500 to 800 nm.
[0096] TEM characterization of sample 7# was performed, and the results are as follows Figure 4 As shown, it indicates that the nanosheet morphology is still maintained after calcination at 450°C.
[0097] Carbon monoxide preferential oxidation performance test
[0098] The hydroxy nickel magnesium silicate catalyst loaded with precious metals is placed in a U-shaped tube and heated in a reactor to test its performance at different temperatures. The gas after the subsequent reaction is mainly detected by a gas chromatograph equipped with a TCD detector. Evaluate its activity. The catalyst dosage is 50 mg, and the gas composition (in volume percentage): 1% CO, 1.25% O2, 50% H2, and He balance. Test temperature range: 30-200°C; reaction space velocity is 60000h -1 The results are as follows Figure 5 shown.
[0099] from Figure 5 It can be seen that sample 7# can achieve complete conversion of CO at 70°C and maintain a wide temperature operating window of 200°C. Sample 7# is significantly better than representative samples 1#~6# and 8#~10#.
[0100] Sample 7# was tested for stability according to the above catalytic test conditions, with a reaction temperature of 100°C. The results are as follows: Figure 6 As shown, the CO conversion rate can still be maintained above 99% at 100°C after 50 hours.
[0101] Table 1 lists the performance comparison of the catalysts prepared using samples 1# to 10# of the present invention as carriers and the catalysts prepared using existing oxide carriers. Note: The temperature operation window in Table 1 refers to the temperature range in which the CO conversion rate is 100%, that is, CO can be completely converted within the corresponding temperature range.
[0102] Table 1 Catalyst performance comparison chart.
[0103]
[0104]
[0105]
[0106] It can be seen from Table 1 that compared with other samples, sample 7# has the best CO preferential oxidation performance, which is specifically manifested in that CO can be completely converted at a low temperature of 70°C. It also has the widest temperature operating window (70-200°C) and excellent stability.
[0107] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A hydroxyl-rich nickel magnesium silicate nanosheet material, comprising hydroxyl-rich nickel magnesium silicate nanosheets, wherein the surface of the hydroxyl-rich nickel magnesium silicate nanosheets contains hydroxyl groups and NiO; the chemical formula of the hydroxyl-rich nickel magnesium silicate nanosheets is shown in Formula 1: (Ni x Mg 1-x )2Si2O5(OH)4 Formula 1; in, x is 0.45 to 0.55; According to X-ray photoelectron spectroscopy analysis, the relative content of hydroxyl groups in the hydroxyl-rich nickel magnesium silicate nanosheet material is 70-75%, and the relative content of NiO is 25-30%.
2. The hydroxyl-rich nickel magnesium silicate nanosheet material according to claim 1, characterized in that: The relative content of hydroxyl groups obtained by XPS fitting is greater than 50% and less than 100%, and the relative content of NiO is greater than 0 and ≤50%.
3. The hydroxyl-rich nickel magnesium silicate nanosheet material according to claim 1 or 2, characterized in that: The lateral size of the hydroxyl-rich nickel magnesium silicate nanosheet is 500-800 nm.
4. The method for preparing the hydroxyl-rich nickel magnesium silicate nanosheet material according to any one of claims 1 to 3, characterized in that: The following steps are involved: A water suspension of silicon dioxide, a soluble magnesium salt, a soluble nickel salt, an acid solution and a hydroxide solution are mixed, and the resulting mixture is subjected to a hydrothermal reaction to obtain a hydroxyl-rich nickel magnesium silicate nanosheet material precursor; the molar ratio of Ni in the soluble nickel salt to Mg in the soluble magnesium salt is x:(1-x), wherein x is 0.45 to 0.55; The hydroxyl-rich nickel magnesium silicate nanosheet material precursor is calcined to obtain the hydroxyl-rich nickel magnesium silicate nanosheet material; the calcination temperature is 400-500°C.
5. The preparation method according to claim 4, characterized in that: The molar ratio of silicon dioxide to Ni in the soluble nickel salt is (0.75-3.75):1; The molar ratio of the silicon dioxide to the hydroxide in the hydroxide solution is 3:(4-8); The acid solution includes a boric acid solution; the molar ratio of the silicon dioxide to the boric acid in the boric acid solution is (1-2):
5.
6. The preparation method according to claim 4 or 5, characterized in that: The temperature of the hydrothermal reaction is 160-200° C., and the time is 12-24 hours.
7. The preparation method according to claim 4, characterized in that: The heat preservation time of the calcination is 5 to 12 hours.
8. Use of the hydroxyl-rich nickel magnesium silicate nanosheet material according to any one of claims 1 to 3 or the hydroxyl-rich nickel magnesium silicate nanosheet material prepared by the preparation method according to any one of claims 4 to 7 as a catalyst carrier.
9. A supported noble metal catalyst, characterized in that: It comprises a carrier and a noble metal loaded on the carrier; the carrier is the hydroxyl-rich nickel magnesium silicate nanosheet material according to any one of claims 1 to 3 or the hydroxyl-rich nickel magnesium silicate nanosheet material prepared by the preparation method according to any one of claims 4 to 7.
10. Use of the supported noble metal catalyst according to claim 9 in CO preferential oxidation reaction.